Integrated strategies to tackle the inequitable distribution of doctors in Thailand: four decades of experience - Pengpaibon Paichit; Wibulpolprasert Suwit (BMC, 2003)
Abstract Inequitable distribution of doctors with high concentration in urban cities negatively affects the public health objective of Health for All. Thus it is one of the main concerns for most health policy makers, particularly in developing countries. This paper aims to summarize strategies to solve inequitable distribution of human resources for health (HRH) between urban and rural areas, by using four decades of experience in Thailand as a case study for analysis.